1976
DOI: 10.1002/app.1976.070200615
|View full text |Cite
|
Sign up to set email alerts
|

A study of foam extrusion using a chemical blowing agent

Abstract: SynopsisAn experimental study of foam extrusion was carried out to determine the effect of processing variables on the quality of the foam produced. For the study, the chemical blowing agent azodicarbonamide was used, together with an activator and a nucleating agent, to produce thermoplastic foams of low-density polyethylenes. The quality of foam was determined from photomicrographs and the tensile properties of extrudate samples. It was found that the percent elongation correlates with the foam density and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 1 publication
0
26
0
Order By: Relevance
“…The total extrusion pressures of Vulcan XC72 filled, microcellular, uncured and cured compounds are 4 12.296 130 62 EB 5 12.296 130 80 EB 4 12.296 140 87 EB 5 12.296 140 113 EB 6 12.296 140 54 EB 7 12.296 140 76 EB 8 12.296 140 88 EB 7 7.685 140 93 EB 7 23.055 140 60…”
Section: Total Extrusion Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…The total extrusion pressures of Vulcan XC72 filled, microcellular, uncured and cured compounds are 4 12.296 130 62 EB 5 12.296 130 80 EB 4 12.296 140 87 EB 5 12.296 140 113 EB 6 12.296 140 54 EB 7 12.296 140 76 EB 8 12.296 140 88 EB 7 7.685 140 93 EB 7 23.055 140 60…”
Section: Total Extrusion Pressurementioning
confidence: 99%
“…[3][4][5] They concluded that the bubble size and void fraction increase with temperature, reducing the extrusion rates and die length/diameter ratio under constant extrusion rate conditions. An important aspect of foam extrusion is the mechanics of bubble growth in the polymer matrix.…”
Section: Introductionmentioning
confidence: 97%
“…If we further assume that the gas bubbles in each cross section have enough time to grow to equilibrium dimensions at any pressure below the critical level (P < Per), the ~p quantity in Equation (8) can be determined with the aid of the following equation:…”
Section: Practical Calculations and Recommendationsmentioning
confidence: 99%
“…Studies of bubble development and morphology of polymers in foaming extrusion processes and the effect of processing variables on the quality of the produced foams have been reported by several authors [3][4][5].…”
Section: Introductionmentioning
confidence: 98%